Managing maturity in process-based improvement organizations: a perspective of the Romanian companies - Păunescu, Carmen; Acatrinei (Pantea), Carmen (Journal of Business Economics and Management, 2012)
Building upon various models from the literature which assess the maturity level achieved by an organization at one moment in time, the paper introduces a model which helps organizations, interested in remaining competitive and achieving sustainability, to monitor and evaluate their process performance. Such as, the paper analyzes the relationships that exist among the critical components of an organization's management system at the strategic and operational level so that key drivers will become the heart of sustainable development. In particular, the paper focuses on how the organizational system influences process maturity profile of the Romanian companies. Data were collected in face-to-face structured-questionnaire interviews from 1302 public and private organizations from Romania. The dearth of empirical research examining organization process maturity in emerging countries constitutes a critical gap in the business process management literature that needs much more attention from scholars. For the purpose of this paper, a factor analysis was employed to explain the pattern of correlations within a set of observed variables that determine the process maturity profile of the Romanian companies. The research results show that there are strong positive correlations between the variables examined that account for a higher level of maturity and performance of organization's processes.